2021
DOI: 10.52964/amja.0849
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic visualization of facial vasoconstriction is associated with 30-day all-cause mortality in medical patients; prospective observational two-site cohort study

Abstract: Introduction: Quick and reliable assessment of acute patients is required for accurate triage. The temperature gradient between core and peripheral temperature could possibly instantly provide information on circulatory status. Methods: Adult medical patients, who did not receive supplementary oxygen, attending two emergency departments, had a thermographic image taken on arrival. The association between 30-day mortality and gradients was tested using logistic regression. Results: 726 patients were studied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 11 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Research has been conducted to investigate the most optimal reference point for measuring the peripheral temperature. The research concluded that the tip of the nose was the most accurate reference point when compared with the third finger and the ear lobes (Holm et al, 2018;Jensen et al, 2021a).…”
Section: The Initial Analysismentioning
confidence: 99%
“…Research has been conducted to investigate the most optimal reference point for measuring the peripheral temperature. The research concluded that the tip of the nose was the most accurate reference point when compared with the third finger and the ear lobes (Holm et al, 2018;Jensen et al, 2021a).…”
Section: The Initial Analysismentioning
confidence: 99%
“…2 In a prospective study of 726 patients they demonstrated that the temperature gradient between nose and eye could help identify variations in skin perfusion and was predictive Evolve, Adapt, Innovate and Deliver: Acute Medicine post COVID pandemic of all cause 30 day mortality. 3 This requires further study but may become a further useful tool in the assessment of physiology of acute unwell medical patients. Dutch colleagues prospectively studied 1328 patients presenting acutely with infective illnesses.…”
Section: Editorialmentioning
confidence: 99%
“…The proportion of studies with a low-risk rating for concerns around the applicability of their findings in the patient selection, index test and reference standard domains were 73, 57 and 77%, respectively. Ten studies scored low risk ratings across all domains (11,12,18,20,24,25,27,30,36,39). One scored high-risk ratings across all domains (16).…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The majority of authors identified their studies as exploratory or assessing feasibility (n = 16) (11, 12, 14-16, 19, 21, 22, 26, 27, 31, 32, 34, 35, 37, 39). Few were described as validation or diagnostic accuracy studies (n = 8) (13,17,18,20,24,33,36,38).…”
Section: Stage Of Developmentmentioning
confidence: 99%
See 1 more Smart Citation